2015
DOI: 10.1155/2015/540731
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-Frequency Vibratory Stimulation Regulates the Balance between Osteogenesis and Adipogenesis of Human Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Osteoporosis can be associated with the disordered balance between osteogenesis and adipogenesis of bone marrow-derived mesenchymal stem cells (BM-MSCs). Although low-frequency mechanical vibration has been demonstrated to promote osteogenesis, little is known about the influence of acoustic-frequency vibratory stimulation (AFVS). BM-MSCs were subjected to AFVS at frequencies of 0, 30, 400, and 800 Hz and induced toward osteogenic or adipogenic-specific lineage. Extracellular matrix mineralization was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…To investigate these ends, intermittent shear stress and cyclic hydrostatic pressure have been shown to elicit mechanosensitive gene profiles in MSCs and further work has shown enhanced production of bone ECM using pulsatile versus fixed hydrostatic shear flow [112, 113]. Interestingly, high acoustic frequencies will also guide MSCs toward osteogenesis and spare the adipogenic induction seen at lower frequencies [114], and larger three-dimensional pore size will elicit more osteogenic differentiation [111]. Analogous to earlier lessons unveiled by Brietbach et al, endocardial valve ossification has been observed when MSCs encounter the required inductive mechanical stress [9, 115].…”
Section: Regenerative Goalsmentioning
confidence: 99%
“…To investigate these ends, intermittent shear stress and cyclic hydrostatic pressure have been shown to elicit mechanosensitive gene profiles in MSCs and further work has shown enhanced production of bone ECM using pulsatile versus fixed hydrostatic shear flow [112, 113]. Interestingly, high acoustic frequencies will also guide MSCs toward osteogenesis and spare the adipogenic induction seen at lower frequencies [114], and larger three-dimensional pore size will elicit more osteogenic differentiation [111]. Analogous to earlier lessons unveiled by Brietbach et al, endocardial valve ossification has been observed when MSCs encounter the required inductive mechanical stress [9, 115].…”
Section: Regenerative Goalsmentioning
confidence: 99%
“…These molecules are often used as markers in the evaluation of osteogenic differentiation in vitro and in vivo [13]. Peroxisome proliferator-activated receptor gamma 2 (PPAR γ 2) has been described as an adipocyte-specific marker [14]. Thus, these markers can be used in monitoring the balance between osteogenesis and adipogenesis of BMSCs in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) are non-hematopoietic stem cells in the bone marrow which are derived from the mesoderm; they can self-proliferate and are capable of multi-directional differentiation (3). A BMSC is a type of adult pluripotent stem cell, isolated and cultured from the bone marrow, which can be found in different species such as chickens, rats, rabbits, dogs and other animals as well as humans (4).…”
Section: Introductionmentioning
confidence: 99%